2015
DOI: 10.13005/bbra/1852
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Analysis of Vehicles Pollutant Emissions Reduction Technologies

Abstract: The article covers analysis of the technical measures, aimed at meeting the requirements on motor vehicles harmful substances emissions. Assessment estimates of expenses for fulfilling of harmful emissions standards from Euro 4 to Euro 6for light commercial vehicle engine with swept volume 2.0 liter with an aftertreatment system. The articles covers diesel, gasoline and natural gas engines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Article [11], which is a continuation of work [10], analyzed and compared the complexity and cost of the systems for neutralizing the exhaust gases from the diesel engines, as well as from petrol and gas ICEs. It was shown that for these engines to meet the pollutant emission norms within Euro 4 to Euro 6, the complexity and cost of treatment systems substantially increases.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Article [11], which is a continuation of work [10], analyzed and compared the complexity and cost of the systems for neutralizing the exhaust gases from the diesel engines, as well as from petrol and gas ICEs. It was shown that for these engines to meet the pollutant emission norms within Euro 4 to Euro 6, the complexity and cost of treatment systems substantially increases.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In all the models examined, the parameters are considered irrespective of the engine parameters and their relations. Such an approach does not allow evaluating the effectiveness of processes in relation to a specific class of engine and/or a specific engine [29][30][31].…”
Section: General Descriptionmentioning
confidence: 99%
“…Першийце встановлення додаткових прокладок головки блоку циліндрів [1,3], який приводить до суттєвого погіршення екологічних параметрів конвертованого газового ДВЗ. Другийце застосування термодинамічного циклу Міллера, який забезпечує зниження не геометричного, а фактичного ступеня стиснення [4,5]. Але треба зауважити, що застосування циклу Міллера, при якому дизельна форма камери згоряння залишається без змін, не вирішує головної проблеми забезпечення енергоефективної та екологічної роботи газового ДВЗ.…”
Section: вступunclassified